2018
DOI: 10.1186/s12886-018-0673-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between corneal biomechanical properties and structural biomarkers in patients with normal-tension glaucoma: a retrospective study

Abstract: BackgroundWe evaluated the relationships between corneal biomechanical properties and structural parameters in patients with newly diagnosed, untreated normal-tension glaucoma (NTG).MethodsAll subjects were evaluated using an Ocular Response Analyzer (ORA) measuring corneal hysteresis (CH) and the corneal resistance factor (CRF). Central corneal thickness (CCT), Goldmann applanation tonometric (GAT) data, axial length, and the spherical equivalent (SE), were also measured. Confocal scanning laser ophthalmoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
2
20
0
1
Order By: Relevance
“…Limited evidence of a relationship between corneal biomechanical parameters and RNFL has been shown in the literature. 49,[52][53][54] Park et al 49 report no significant association between CCT, CH, or CRF with the mean RNFL thickness, although after adjustment, CH and RNFL were directly associated (ß = 0.013, P = 0.043) in NTG patients. In studies measuring RNFL using OCT, no association was found between CH and CRF, and RNFL thickness in suspect or confirmed OAG, as well as in healthy myopic eyes, 52,53 except for one study in which the relationship between CH and RNFL thickness was significant (ß = 0.2, P = 0.001) in OAG.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Limited evidence of a relationship between corneal biomechanical parameters and RNFL has been shown in the literature. 49,[52][53][54] Park et al 49 report no significant association between CCT, CH, or CRF with the mean RNFL thickness, although after adjustment, CH and RNFL were directly associated (ß = 0.013, P = 0.043) in NTG patients. In studies measuring RNFL using OCT, no association was found between CH and CRF, and RNFL thickness in suspect or confirmed OAG, as well as in healthy myopic eyes, 52,53 except for one study in which the relationship between CH and RNFL thickness was significant (ß = 0.2, P = 0.001) in OAG.…”
Section: Discussionmentioning
confidence: 96%
“…1,24,25,[30][31][32][33]45 Various studies have found associations between these parameters and optic nerve parameters, including rim area. 27,31,34,[46][47][48][49][50][51] More specifically, Jonas et al 51 found a significant correlation between CCT and the neuroretinal rim area (r = 0.13, P < 0.001) as measured from stereo optic disc slides in a cohort regrouping normal, OAG, and OHT eyes. Park et al 49 showed that low CCT, CH, and CRF were associated with a smaller rim area (r = 0.256, P = 0.012; r = 0.347, P = 0.001; and r = 0.227, P = 0.027, respectively), as measured using the HRT (Heidelberg Retina Tomograph), in eyes with normotensive glaucoma (NTG) but not in normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that corneal hysteresis (CH), an indicator of corneal viscoelasticity, is associated with biomechanical properties of the cornea. Some studies showed that CH may be related to the biomechanical characteristics of peripapillary sclera and lamina cribrosa, as they are embryologically developed from the mesoderm and also because the collagen fibers continue with the collagen fibers from the corneal stroma [ 1 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal biomechanics and central corneal thickness were analyzed in NTG but few investigations have been made on corneal nerve in NTG. 33,34 . A whorl-like corneal subbasal nerve plexus in normal eyes was depicted by Utsunomiya T's report which was in the inferocentral area of the cornea 27 .…”
Section: Discussionmentioning
confidence: 99%